THE EFFECTS OF RELATIONSHIP MARKETING ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT PT. MULTI POWER TECHNOLOGY ARCHIPELAGO - Aisyah, Siti (Proceeding International Seminar of Islamic Studies, 2024)
The main objective of this research is to examine the impact of Relationship Marketing on customer loyalty, with customer happiness as a mediating factor, in the context of PT. Multipower Teknologi Nusantara is a company operating in the technology sector in Indonesia. Both directly and indirectly. This research uses quantitative methodology and statistical analysis, namely the use of partial least squares structural equation models (PLS-SEM) to carry out route analysis, including latent variables. Research findings show that Relationship Marketing has a statistically significant and beneficial impact on customer loyalty in the PT industry. Multipower Teknologi Nusantara The impact of Relationship Marketing on PT Multidaya customer satisfaction Teknologi Nusantara is profitable and statistically significant. The impact of customer satisfaction on customer loyalty among PT Multidaya customers Teknologi Nusantara is positive and strong. There is no visible mediating or moderating effect of customer satisfaction on the relationship between Relationship Marketing and customer loyalty. The resulting corrected R-square value for the customer satisfaction variable is 0.375. This means that Relationship Marketing accounts for 52.5% of the variation in client loyalty. Therefore, the model is categorized as moderate.